PENGARUH KECEMASAN PANDEMI COVID-19 TERHADAP PENGELUARAN ASI IBU POST PARTUM DI PUSKESMAS PEMBANTU LAMBUR II KABUPATEN TANJUNG JABUNG TIMUR PROVINSI JAMBI TAHUN 2022 - Nia Nurzia; Martang (SCIENTIA JOURNAL, 2022)
Background: The Covid-19 outbreak has become a global pandemic, in Indonesia because total people infected with the Covid-19 virus experience enhancement day by day , condition the could make problem by psychological for Mother pregnant and Mother postpartum , which can cause anxiety , if atmosphere heart Mother feel no comfortable even worried so will hinder smooth milk production. Study this aim for knowing influence worry covid-19 pandemic against mother 's milk production post partum at Puskesmas Servant Lambur II District Cape Jabung East Jambi Province in 2022. Method : Study is study quantitative with design cross sectional. Population as many as 20 people and sample in study this 20 people are taken by total sampling. Study this implemented on date 01 February – 01 March 2022. Analysis of the data used is Analysis Univariate and Bivariate use test chi-square . Conclusion: Results study show that part big Mother post partum worried facing the covid-19 pandemic , as many as 12 people (60 % ) , some big mother's milk post partum no fluent that is as many as 11 people ( 55%) . Based on results statistical test obtained p-value 0.005 (p< 0.05 ) means that there is an effect worry covid-19 pandemic with mother 's milk production post partum at Puskesmas Servant Lambur II District Cape Jabung East Jambi Province Year 2022 with nila OR : 35,000 (2 632 – 465,373) it means Mother anxious postpartum _ have 35,000 times the risk of spending the milk no fluent compared to with mother who doesn't anxious . Suggestion : should Public health center Servant Lambur II District Cape Jabung East increase communication to Mother post partum about maintenance breast and good nutrition _ as well as repair condition psychological for increase milk production .